Threatened Abortion and its Burden - Khatun, Mst Hosna Ara (Journal of Dhaka National Medical College & Hospital, 2020)
Threatened Abortion is the most common cause of first trimester bleeding and is the most common reason for general practitioner's emergency gynaecology referral. First-trimester bleeding may indicate an underlying placental dysfunction. This may manifest later in pregnancy causing adverse outcome affecting both mother and the baby and most commonly associated with abortion, pre-maturity, low birth weight, respiratory distress syndrome and intra uterine growth retardation. Vaginal bleeding in early pregnancy is a common condition that adds stress and anxiety to pregnant women. Therefore, obstetricians are regularly dealing with such cases whether it is in an out-patient clinic or emergency setting. So pregnancies complicated by threatened abortion constitute a risk group requiring careful obstetric and perinatal supervision and follow-up. J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 31-36